Trends in emergency higher education digital transformation during the COVID-19 pandemic - Mospan, Natalia (Journal of University Teaching and Learning Practice, 2023)
The article reveals trends in emergency higher education digital transformation during the COVID-19 pandemic. Due to the enormous amount of literature discussing global higher education responses to the Coronavirus, the preference is given to publications with a systematic literature review published in 2021. The period indicates the end of the 2-nd wave of the pandemic and the lessons learnt. However, case studies were also the focus of attention, primarily used for a convincing illustration of the trends in a particular country. Moreover, descriptive survey research allows empirical evidence of 468 students and 179 lecturers from four Ukrainian universities and highlights the theoretical insights. The analysis of cross-cultural investigations, systematic literature reviews, case studies, and empirical data from four Ukrainian HEIs makes it possible to receive experience from 30 countries about their responses to the COVID-19 pandemic in 2020-2021. This massive amount of evidence reveals universal consequences for higher education caused by the COVID-19 pandemic and shapes trends in emergency higher education transition to digital format. The findings show that the emergency higher education transition to digitally-based education during 2020-2021 worldwide is characterised as diverse and unprepared. In the case of Ukraine, the empirical data collected from four national HEIs situated in different regions of the country gives grounds for the following insights: 1) in response to the challenges of the COVID-19 pandemic, the national HEIs show trends similar to global higher education; 2) university teachers have considerable responsibility in transitioning traditional teaching methods into a virtual educational environment and have successfully coped with this challenge; 3) universal trends in higher education are observed on the national level, while there is diversity on the institutional level among national HEIs; 4) there is an opposite attitude of lecturers and generation Z students to the preference for the educational mode in the future.